MENENTUKAN NILAI EIGEN DAN VEKTOR EIGEN DARI MATRIKS TRIDIAGONAL - Sari, Nur Meliana; Gemawati, Sri; Sirait, Asli (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses how to obtain eigenvalues and their corresponding eigenvectors of tridiagonal matrices, of the form     a bca bb cb cAnnn 1121 210 00 0 000 00 0 0         where  , , b are number complex and  is mapping from a set of integer from 1 to n-1 into a nonnegative integer.